Production of biodiesel from sludge palm oil by esterification process - Hayyan, Adeeb; Alam, Md. Zahangir; Mirghani, Mohamed Elwathig Saeed; Kabbashi, Nassereldeen Ahmed; Hakimi, Noor Irma Nazashida Mohd; Siran, Yosri Mohd; Tahiruddin, Shawaluddin (David Publishing, USA, 2010)
Sludge palm oil (SPO) is an attractive feedstock and a significant raw material for biodiesel production. The use of SPO can lower the cost of biodiesel production significantly. In this study biodiesel fuel was produced from SPO by esterification process using P-toluenesulfonic acid (PTSA) as acid catalyst in different dosages in presence of methanol to convert free fatty acid (FFA) to fatty acid methyl ester (FAME). Batch esterification process of SPO was carried out to study the influence of PTSA dosage (0.25-10% wt/wt),molar ratio of methanol to SPO (6:1-20:1), temperature (40-80 oC), reaction time (30-120 min). The effects of those parameters on the yield of crude biodiesel and conversion of FFA to FAME were monitored. The optimum condition for batch esterification process was 0.75% wt/wt, 10:1 molar ratio, 60 oC temperature and 60 minutes reaction time.